2019
DOI: 10.21273/hortsci13735-18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vacuum Packaging on Enzymatic Browning and Ethylene Response Factor (ERF) Gene Expression of Fresh-cut Lotus Root

Abstract: Ethylene response factor (ERF) genes have been involved in responses to biotic and abiotic stress, including hypoxia and anaerobic stress. Vacuum packaging (a typical anaerobic stress) is an effective storage method used to delay browning of fresh-cut lotus root (Nelumbo nucifera). In model plants, ERF genes have been identified as responsive to hypoxia. Whether ERF is associated with browning of vacuum-packaged lotus root has not been studied. The effects of vacuum packaging on browning, phenolic content, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
8
14
0
Order By: Relevance
“…By determining the BD in storage after using two different packaging methods, it was clear that the BD of the samples subjected to VP (anaerobic stress) was significantly less than that of the control group. These results confirmed and extended our previous finding (Min et al, 2019).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…By determining the BD in storage after using two different packaging methods, it was clear that the BD of the samples subjected to VP (anaerobic stress) was significantly less than that of the control group. These results confirmed and extended our previous finding (Min et al, 2019).…”
Section: Resultssupporting
confidence: 93%
“…Changes in PAL, PPO, and POD enzymatic activity in storage under two different packaging methods were analyzed. These results showed that PAL, PPO, and POD activity were inhibited during VP, which occurred in parallel with less significant browning during storage, which was consistent with previous reports (Min et al, 2019), NNPAL, NNPPO, AND NNPOD GENE EXPRESSION. There was an obvious differential response to different packaging methods for the two PAL, two PPO, and seven POD genes.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations